Diagnostic of f(R) under the Om(z) function - Jaime, Luisa G. (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
We perform the two-point diagnostic for the Om(z) function proposed by Sahni et al. in 2014 for the Starobinsky and the Hu and Sawicki models in f(R) gravity. We show that the observed values of the Omh2 function can be explained in f(R) models, while in ΛCDM the Omh2 function is expected to be a redshift independent number. We perform the analysis for some particular values of Ω0m, finding a cumulative probability (P(χ2≤χ2model)) P∼0.16 or ∼0.09 for the better cases versus a cumulative probability of P∼0.98 in the ΛCDM scenario. We also show that these models present a characteristic signature around the interval between z∼2 and z∼4 that could be confronted with future observations using the same test.